A New Fluid-Structure Interaction Solver in OpenFOAM - Do, Quoc Vu; Pham, Van Sang (Old Journal, 2019)
In this article, we introduce a new numerical solver for the Fluid-Structure Interaction problem. The solver is developed using Immersed Boundary Method (IBM) integrated into OpenFOAM environment. The velocity-pressure coupling is implemented via modifying the PISO algorithm of OpenFOAM. The solver can solve for the interaction of multiple structures in fluid flow. The collision of structures is simulated using an elastic repulsive force model. A parallel algorithm is developed to make the solver able to run on parallel computer system, structures can move from a partition to another partition. The solver was validated and applied in solving the real problem.